The use of acupuncture in first aid of burns-Clinical report - Loskotova, A; Loskotova, J (Burns, 2017)
Burns are a very painful skin injury, or injury of soft tissues. The development of post-traumatic stress disorder can develop, even in those with minor injuries (Ia-IIb degree). Development of problems is very rapid and intense since, according to developmental embryology, the skin and central nervous system (CNS) descend from the same germ layer-ectoderm. This clinical report presents the results acquired from the data of 1008 patients suffering from burns treated by the acupuncture (ACU)-from 1983-2015 in the surgery ward of the hospital in Vysoke Myto in the Czech Republic. The data of 1008 patients were processed and evaluated. 1. The report demonstrates a positive effect of ACU treatment signs on the skin were monitored, i.e. reddening, pigmentation, scars. During the treatment the elimination of many of these signs was observed. Improvement of healing process and improvement in the final wound healing were evaluated and shown by the statistical method-the χ2 test. For demonstrating the effect of ACU treatment of BT the Pearson's and the Cramer's contingency coefficient were examined. 2. The time of the first application of the ACU treatment after burn was followed and evaluated with a random set. The best results were achieved when the first ACU treatment was applied as soon as possible after BT injury (ideally immediately, optimally within 48h). The positive effect of ACU on burns is medical, economical and biopsychosocial.
Keywords: senioři; Wound Healing; First Aid; popálení; Post-traumatic stress (PTS); senioři nad 80 let; psychický stres; Acupuncture (ACU); Retrospective Studies; kojenec; mladiství; Middle Aged; mužské pohlaví; Burn trauma (BT); Infant; Large intestine point 4 (LI 4); Adult; mladý dospělý; Stress, Psychological; hojení ran; dítě; Child; Burns; Aged, 80 and over; Child, Preschool; Young Adult; Large intestine point 11 (LI 11); ženské pohlaví; Lung point 7 (LU 7); retrospektivní studie; předškolní dítě; Humans; Pain Management; Stress Disorders, Post-Traumatic; Wound healing; Acupuncture Therapy; First aid; lidé středního věku; akupunkturní terapie; posttraumatická stresová porucha; jizva hypertrofická; management bolesti; první pomoc; Cicatrix, Hypertrophic; dospělí; Female; Aged; Scar; Adolescent; lidé; Male